Effect of ability on freestyle swimbench stroke charateristics - Spigelman, T. H.; Uhl, T. L.; Mullineaux, D. R.; Cunningham, T. J.; Mair, S.; Shapiro, R. (2008 Annual Meeting (NACOB) Ann-Arbor, 2008)
Elite level swimmers are distinguished from non-elite swimmers by longer stroke lengths (SL) and faster stroke rates (SR), and decreased lag time between propulsive phases during freestyle defined by the Index of Coordination (IdC) (Seifert et al., 2004). Motor control research suggests elite performers have an enhanced ability to reorganize the sensory-motor system as greater constraints are placed on the system (Kelso et al., 1984). In swimmers this means making subtle adjustments in SL, SR, and IdC as necessary (Potdevin et al., 2006, Seifert et al., 2007). Coaching swimmers poses a challenge in that the majority of technique is obscured by occurring under the water. A swimbench, designed to reproduce the biomechanical and physiological demands of swimming, may assist coaches in observing technique. This study investigated the spatial-temporal, coordinative structures and kinematics of different ability levels swimmers on a dryland swimbench. Information gained from this research would provide evidence to support the use of a dryland device to coach swimming.